E.P.B. correspondence - E. P. B., active 1865.
ALS (1865 April 31; Lincoln, Mass.) addressed to George from E.P.B. concerning reaction to the assassination of Abraham Lincoln and Robert E. Lee's surrender at Appomattox, Va. Other topics include stamp collecting and social activities in Lincoln, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lee, Robert E. -- 1807-1870.; Lincoln, Abraham, -- 1809-1865 -- Assassination; Stamp collecting; Lincoln (Mass.) -- Social life and customs; United States -- History -- Civil War, 1861-1865 -- Peace; Appomattox (Va.) -- History -- Civil War, 1861-1865.